IMF reform in the aftermath of the global financial crisis: Let the IMF speak truth to power - Matthias Lücke (The crisis and beyond, 2009)
In response to the worldwide financial crisis, many countries have put together fiscal stimulus packages of substantial size comprising increases in public spending, tax cuts, and transfers to the private sector. These packages vary considerably in respect to size, composition, and timing. Particularly large packages have been adopted by the United States and China, but also by Germany which took the leading role in European fiscal expansion. There are also marked differences in the structure of the stimulation packages. While developing countries provide fiscal stimulus almost exclusively via increases in spending, one-third of the packages in industrialized countries takes the form of tax cuts. Concerning the time pattern, most packages envisage the measures to focus on 2009 and 2010. In some countries, such as the United States and China, the fiscal stimulus is planned to reach its peak only in 2010.
Keywords: 330; Internationales Währungssystem; Reform; Finanzmarktkrise; Internationaler Finanzmarkt; Regulierung; Welt